Introduction of vehicle communication and intelligent traffic management systems - Makó, Dávid; Cservenák, Ákos (Advanced Logistic Systems - Theory and Practice, 2023)
Nowadays, the vehicle industry is heading for a significant change. There are fundamental debates about what type of drive would be ideal for vehicles in terms of environmental awareness, because environmental protection has become one of the main directions in vehicle production, especially due to the fluctuating raw material sources in today's uncertain situation. Another issue that is at least as important is traffic safety. Almost everyone agrees that the way to safer traffic is mainly through the development of vehicle communication. This is a direction that develops in all vehicles, regardless of drive, construction, or performance. There are several types of vehicle communication systems, but it is not easy to categorize these systems, as it is difficult to clearly separate them, as there are quite large overlaps between them. This article provides an overview of these vehicle communication systems.